Influence of pitfall trap funnel orientation on insect abundance in trap crop - Musa, Nadia Nisha; Zulkipli, Husna; Md Norizzan, Alisha Umairah; Azhari, Nur Alya Natasha; Mukhtar, Hazwani Husna; Zulkifli, Muhammad Redzuan; Arif, Aniq Hassif; Ahmad Fauzi, Nurul Ameera (2025)
Pitfall trap is a widely used method in ecological research for passive sampling of ground-dwelling insects. The efficiency of a pitfall trap can be influenced by many physical factors, including the trap design. The present study was conducted to determine the influence of funnel orientation of the pitfall trap for the insect collection at a banana crop site, a type of trap crop, at Universiti Teknologi MARA, Perak Branch, Tapah Campus. The sampling was performed using different designs of funnel orientations, i.e., upward funnel, downward funnel and multiple funnels, with the standard design without a funnel served as the control group. The abundance of collected insects was analysed using Microsoft Excel 2007. Based on the results, the pitfall trap effectively captured a diverse assemblage of insect orders, with Orthoptera (40%), Hymenoptera (21%) and Diptera (13%) being the most common orders. Overall, 21 families representing 11 orders were recorded, with Gryllidae (20.51%), Acrididae (10.99%) and Formicidae (10.79%) identified as the most common families. The influence of different funnel orientations indicated that the downward funnel captured a higher abundance of insects than the other funnel orientations. However, the result also indicated that the control group of the pitfall trap (no funnel) captured more insects than the treatment groups. These findings suggest that optimisation in trap design can further improve data accuracy in ecological studies. This study provides practical suggestions for the improvement of biodiversity monitoring techniques in tropical ecosystems.